x+3(-19/11)=-6

Simple and best practice solution for x+3(-19/11)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3(-19/11)=-6 equation:



x+3(-19/11)=-6
We move all terms to the left:
x+3(-19/11)-(-6)=0
We add all the numbers together, and all the variables
x+6+3(-19/11)=0
We multiply parentheses
x+6-19/11*3=0
We multiply all the terms by the denominator
x*11*3-19+6*11*3=0
We add all the numbers together, and all the variables
x*11*3+179=0
Wy multiply elements
33x*3+179=0
Wy multiply elements
99x+179=0
We move all terms containing x to the left, all other terms to the right
99x=-179
x=-179/99
x=-1+80/99

See similar equations:

| 1/2x+8-6=4 | | 11x+15=5x-19 | | -(8+3x)+5=2x+5 | | .30x+140=x | | 3(x+2)+9=42 | | -10k−6=9−7k−8k | | -(8+3x)+5=2x | | 41-21x+12x=44 | | 3y+9=9 | | 3(7x-5)+3(6-4x)-4(2x+4)=-4 | | 36(-3)+x-55=-156 | | 2n-4=6+4n | | 5(x)+24-65=79 | | -4=6+2n | | 6(-3v+1)=5(-22 | | 2(5x-3)-(2x-4)=5-(6x=1) | | 66=3u+15 | | -0.4n=3.2 | | (15x+3)=108° | | -12=-48v | | 9x-40=8x+40 | | 7p+8=5p+4p | | 3(5+c)=2(c-5 | | 10=2u-16 | | r-26=-46 | | 2(4Z-11)=3(3z+11)-z | | 8p+4p=12 | | -2(z-8)=1/4(12z+4) | | -1/2=-3/5y+4/5 | | 7p-5=9p+8 | | 1+2x3+4x5=65 | | 3d-13=113d |

Equations solver categories